Report of the Managing Director to the International Monetary and Financial Committee on the IMF's Policy Agenda. (Policy Papers; Policy Paper ;, 2007)
This report reviews the work of the Fund since the 2007 Spring Meetings and the priorities for the period ahead. Progress has been made in the past few months with respect to the framework for surveillance and its implementation, quota and voice, and the Fund's income model. Other key aspects of the MTS have also advanced, including with regard to Bank-Fund collaboration and the Fund's role in low-income countries. Future work will focus on completion of the quota and voice reform, reaching agreement on the Fund's new income model, and delivering budgetary restraint, as well as addressing the evolving challenges facing the Fund and the world economy, notably the financial market turbulence and financial globalization. The paper reports on recent developments in the global economy (Section II) and progress in the following key areas: reshaping surveillance (Section III); emerging market economies and crisis prevention (Section IV); the role of the Fund in low-income countries (Section V); quota and voice issues (Section VI), building institutions and capacity (Section VII); and managing an effective institution (Section VIII).